Ars 83 Helsinki. - Ars 1983 (Helsinki : Ateneum - The Fine Arts Academy of Finland, 1983)
Abakanowicz ; Abramovic / Ulay ; Acconci ; Andre ; Anselmo ; Appelt ; Aycock ; Baselitz ; Becher/Becher ; Berthot ; Beuys ; Borofsky ; Breivik ; Buren ; Cane ; Charlonnai ; Chia ; Clemente ; Cragg ; Dibbets ; van Elk ; Flanagan ; Flavin ; Fridfinnsson ; Fulton ; Graubner ; Green ; Gudmundsson ; Hantaï ; Hilliard ; Hunt ; Hafström ; Judd ; Kawara ; Kelly ; Kiefer ; Kirkeby ; Kirschenbau ; Kosuth ; Kounellis ; Kaks ; Laib ; Le Gac ; LeWitt ; Long ; Lüpertz ; Mach ; De Maria ; Martin ; Merz ; Morellet ; Paik ; Paladino ; Penck ; Pyramiderna ; Rainer ; Rothenberg ; Rückriem ; Ryman ; Schoonhoven ; Serra ; Shapiro ; Spagnulo ; Stuart ; Turrell ; Tuttle ; Twombly ; U-Fan ; Walker ; Willis ; Anderson ; Ashley ; Basil ; Birnbaum ; Bowes ; Byrne ; Chase ; Dougherty ; Eno ; Fitzgerald ; Foreman ; Gilbert & George ; Gorewitz ; Hill ; Jonas ; Marton ; McMahon ; Miller ; Rosler ; Sanborn ; Scroggins ; Smith ; Steinberg ; Twin Art ; Viola ; Weiner
Ars 83 Helsinki, Ateneum - The Fine Arts Academy of Finland, Helsinki, 1983
boek